2020
DOI: 10.1136/bmjopen-2020-039278
|View full text |Cite
|
Sign up to set email alerts
|

Impact of incarceration on cardiovascular disease risk factors: a systematic review and meta-regression on weight and BMI change

Abstract: ObjectiveCardiovascular disease is an underappreciated issue in prison medicine. Recent studies have revealed a higher prevalence of cardiovascular disease risk factors (CVDRFs) among individuals in prison, but the impact of incarceration on CVDRFs over time is not well understood. This review aimed to assess available literature and quantify the relationship between incarceration and trends in major CVDRFs in high-income countries.DesignSystematic review following the Preferred Reporting Items for Systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 65 publications
2
16
0
9
Order By: Relevance
“…The hypothesized relationship may be mediated through CVD risk factors included in the multivariable models, which explains the attenuation after adjustment. For example, a 2020 systematic review of 26 longitudinal studies demonstrated that incarcerated individuals were gained, on average, 5.3 kg (95% CI: 0.5–10.1 kg) in weight during their period of incarceration, though the trends in other risk factors were less clear [ 12 ]. Second, losses to follow-up among Black men were higher than among other sex-race groups, and up to 65% of those losses at later examinations may have been due to incarceration [ 13 ], which limits the ability to capture non-fatal cardiovascular disease events occurring during incarceration, including among those with a history of incarceration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypothesized relationship may be mediated through CVD risk factors included in the multivariable models, which explains the attenuation after adjustment. For example, a 2020 systematic review of 26 longitudinal studies demonstrated that incarcerated individuals were gained, on average, 5.3 kg (95% CI: 0.5–10.1 kg) in weight during their period of incarceration, though the trends in other risk factors were less clear [ 12 ]. Second, losses to follow-up among Black men were higher than among other sex-race groups, and up to 65% of those losses at later examinations may have been due to incarceration [ 13 ], which limits the ability to capture non-fatal cardiovascular disease events occurring during incarceration, including among those with a history of incarceration.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated associations between prior incarceration and higher burden of CVD risk factors and subclinical CVD, including weight gain during incarceration [ 12 ] and incident hypertension and post-release hospitalization due to CVDs [ 4 , 5 ]. For example, CARDIA data demonstrate a 1.7-fold higher odds of incident hypertension and a 2.7-fold higher odds of left ventricular hypertrophy among those with a history of incarceration [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Discussions of ‘health behaviours’ among prison populations include global examinations of the international burden of non‐communicable diseases such as cardiovascular disease, hypertension and diabetes (Herbert et al., 2012; Bondolfi et al., 2020), substance misuse (Baranyi et al., 2019) and mental health (Fazel et al., 2016; Tweed et al., 2019). While food plays an essential role in the physical and mental health of prison populations, it has been somewhat neglected as an area of enquiry by public health researchers and practitioners (Devine‐Wright et al., 2019; WHO, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The state is responsible for providing total healthcare, and, on average, detainees have a higher morbidity rate, which implies greater healthcare needs than non-detained persons [ 13 , 14 ]. To analyze the health condition of prisoners, the literature takes into account, inter alia, indicators, such as BMI, the occurrence of chronic diseases, and addictions [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%